Declining male fertility: investigations into an environmental aetiology using a canine model - Byers, Andrew S. (2017)
Contemporary reports showing negative temporal trends in human sperm quality have provided a weight of evidence, in spite of recognised methodological weaknesses of the early research, strongly indicative of declining male fertility over the past six decades. Other aspects of human male reproductive development, such as hypospadias, cryptorchidism and testis cancer are also showing negative trends in incidence and geographic variation in prevalence. Together these negative changes in parameters of fertility, which have comorbidity, are termed Testicular Dysgenesis Syndrome (TDS). The relative short time period of the trend data and the spatial heterogeneity of these factors suggest an environmental aetiology. Two neighboring and ethno-linguistic similar countries, Denmark and Finland, are used as evidence of this as Denmark has significantly decreased sperm quality as well as an increased incidence of other aspects of TDS when compared to neighboring Finland. Additionally, exposure to persistent environmental chemical pollutants has been associated with decreased sperm quality and increases in other components of TDS. The suggested underlying cause of TDS is perturbed foetal/embryonal programming and reproductive development. In spite of overall poor epidemiological information and a paucity of empirical research data from companion animals there are suggestions that environmental pollutants are affecting the health of cats and dogs. Indeed, the dog may be a relevant research model as it shares our environment and ill health associated with it, such as human TDS. Based on the evidence of environmental pollutants affecting human and animal reproductive development and fertility, this PhD project was developed in order to determine if man’s closest companion, and the animal which wholly shares our environment, demonstrates any parallel reproductive impairment. Specifically, this thesis aims to investigate negative temporal trends related to canine fertility, determine the presence of and geographic variation in tissue concentrations of exemplar environmental pollutants and examine testes tissue and sperm cells, via culture and histology, for association between chemical concentrations and quantitative assessments. Canine testes were collected from three countries; UK (n = 58), Finland (Helsinki region) (n = 20), Denmark (Copenhagen region) (n = 10). These samples were tested for concentrations of three representative chemical groups: PCBs, PBDEs, DEHP. Samples of commercial dog food (n = 28), and a range of canine body fluid was also analysed for these same chemical groups. A retrospective analysis of database information from a population of service dogs in the UK was used to determine temporal trends in canine sperm quality and cryptorchidism over a 26 year period. The concentrations of the three chemical pollutant types were additionally analysed against land use with a Geographic Information System (GIS) and two CORINE land use categories: Artificial and Agricultural. These tissues were assessed histologically using histomorphometric scores, CYP11A1 area stained. Canine testes tissue and sperm were cultured with PCB153 and DEHP to determine direct effects of short term exposures to environmental pollutants by assessing testosterone production (testes explant culture), motility (CASA), sperm viability (hypo osmotic swelling test, chromatin integrity, live:dead ratio). Database analysis of service dog fertility reported two components of TDS: negative temporal trends in sperm quality and a concurrent increased incidence of cryptorchidism. Samples of canine testes tissue contained measurable concentrations of three exemplar pollutants (PCBs, PBDEs, DEHP). These pollutants were also largely present in commercial dog food and some were also present in prostatic fluid, full ejaculate and bitches milk. The profile of EDs and concentrations of specific chemicals showed significant variation across three regions of the UK (Southeast, East Midlands, and West Midlands). Notably, concentrations of legacy industrial chemicals (PCBs, PBDEs) were highest in the West Midlands and phthalate (DEHP) was highest in the southeast. The concentrations of DEHP was significantly higher in Artificial land categories compared to tissue collected in Agricultural land use areas (P<0.05). Canine testis samples collected from three international regions contained concentrations of PCBs and DEHP which were significantly higher in the UK (P<0.05) and PBDEs which were significantly higher in Finland (P<0.05). The histomorphometric assessment of testes showed significant variations across the three countries. The quantification of immunohistochemical testis area stained for CYP11A1 from the three countries showed a significant variation (P=0.0001), and tissue from Denmark showed a significant association between area stained and concentrations of DEHP (P<0.05). Tissue exposed, via testes explant culture, to PCB153 and DEHP at two concentrations showed no significant blunting of LH stimulated testosterone secretion. Sperm exposed, via culturing with two environmentally relevant concentrations of PCB153 and DEHP, exhibited significantly increased (P<0.05) and decreased (P<0.05) measures of motility with these chemicals respectively. Additionally sperm viability, measured using the hypo osmotic swelling assay, was significantly reduced in the presence of PCB153 (P<0.05) and a significant increased when cultured with DEHP (P<0.01). Both chemicals significantly increased sperm DNA fragmentation. Additionally, short term exposure to both chemicals significantly reduced the Live:Dead ratio of sperm (P<0.05). Robust, determinative evidence of negative trends in canine sperm quality and incidence of cryptorchidism indicate that canine and human male fertility are decreasing in parallel. An environmental aetiology is supported by the presence of environmental chemicals in canine diet, testes tissue, prostatic fluid and full canine ejaculate. Geographic differences (National and International) in testis chemical profiles and concentrations may equate with reported regional differences in human TDS. In support of this hypothesis, specific canine testis chemical concentrations were associated with histomorphometric scores from the same cohort of samples. Direct effects of PCB153 and DEHP on sperm motility and viability may be indicative of an alternative acute negative effect on male fertility. These data suggest that the dog, while living in a shared environment with humans, exhibits some parameters of TDS and that canine, as well human, male fertility is declining due to exposure to environmental chemicals.